WAAC-1 Gastric Obstruction in Stranded Green Turtle (Chelonia mydas) in Paloh, Kalimantan Barat at February, 9th 2018 - Fidry R Ikhwan; Ida Ayu Dian Kusuma Dewi; Maulid Dio Suhendro; Dwi Suprapti (Hemera Zoa, 2018)
Marine debris has been being global isu for years. It can give negative impact to the animal in marine environment. One of Indonesian waters who has a serious problem with marine debris is Paloh, West Kalmantan. Mineral bottles that stranded in Paloh beach is not Indonesia production, it printed Malaysia, Singapore, Philippines, Thailand and China label (Saturi, S., 2014). In other word debris that be found in Paloh at least comes frome 5 different counries. Paloh waters also known as home for 4 species of sea turtle, one of them is Green Turtle (Chelonia mydas). Scuyler (2014) said the probablity of green sea turtle to ingest marine debris has increased significantly for more than century, he also said that plastic especially soft plastic in the most comon debris found in sea digestive tract (96.8%).